2020
DOI: 10.1088/1757-899x/833/1/012084
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Water Depth and Flow Velocity on Microstructure, Tensile Strength and Hardness in Underwater Wet Welding

Abstract: Wet underwater welding is a welding process carried out under water. The depth and water flow velocity greatly affect the welding results. Thus, a further research needs to be done about the effect of the depth and water flow velocity of underwater wet welding. The research aimed to determine the effect of depth and velocity of water flow on underwater wet welding on physical and mechanical properties. The welding process is carried out by using SMAW method at a depth of 2.5 m and 5 m with variations in water … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Macro and micro structures of underwater wet welded joints related to water depth and flow have been discussed in our previous papers [18,19]. There are differences in weld penetration depth and porosity due to differences in water depth and water flow speed of underwater wet welding.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…Macro and micro structures of underwater wet welded joints related to water depth and flow have been discussed in our previous papers [18,19]. There are differences in weld penetration depth and porosity due to differences in water depth and water flow speed of underwater wet welding.…”
Section: Resultsmentioning
confidence: 98%
“…It means that the crack in on land weld metals will propagate faster than in underwater wet weld metals. Based on our previous research [19,32], the main microstructure of underwater wet weld metal was acicular ferrite which had small grain and good toughness. It will resist the movement of propagation crack.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Klett et al [14] reported that the amount of hydrogen increases with increasing water depth. The water depth is also responsible for the properties of underwater welded joints, which was studied by Paundra et al [15]. It was stated that the increase of the water depth causes higher hardness in the HAZ.…”
Section: Introductionmentioning
confidence: 97%